Processes of Change in Trauma-Focused Cognitive Behavioral Therapy for Youths: An Approach Informed by Emotional Processing Theory. (March 2021) - Alpert, Elizabeth; Hayes, Adele M.; Yasinski, Carly; Webb, Charles; Deblinger, Esther
In this study, we examined processes of change in trauma-focused cognitive behavioral therapy (TF-CBT) delivered to a community sample of 81 youths. Emotional processing theory (EPT) is used as an organizational framework. EPT highlights activating and changing pathological trauma-related responses and increasing adaptive responses across cognitive, emotional, behavioral, and physiological domains. We coded sessions during the trauma-narration and -processing phase of TF-CBT to examine the extent to which pathological and adaptive trauma-related responses were activated across domains. Higher scores indicate that more domains (range = 0–4) were activated at a threshold of moderate to high intensity. Curvilinear change (inverted U, increase then decrease) in multimodal negative response scores across sessions predicted improvement in internalizing symptoms and symptoms of posttraumatic stress disorder after treatment. Linear increases in multimodal positive responses predicted improvement in externalizing symptoms. Findings suggest value in activating and changing both pathological and adaptive trauma responses across multiple domains and examining nonlinear patterns of change.